Combined Low-/High-Density Modern and Ancient Genome-Wide Data Document Genomic Admixture History of High-Altitude East Asians - Liu, Yan; Wang, Mengge; Chen, Pengyu; Wang, Zheng; Liu, Jing; Yao, Lilan; Wang, Fei; Tang, Renkuan; Zou, Xing; He, Guanglin (Frontiers in Genetics, 2021)
The Tibetan Plateau (TP) is considered to be one of the last terrestrial environments conquered by the anatomically modern human. Understanding of the genetic background of highland Tibetans plays a pivotal role in archeology, anthropology, genetics, and forensic investigations. Here, we genotyped 22 forensic genetic markers in 1,089 Tibetans residing in Nagqu Prefecture and collected 1,233,013 single nucleotide polymorphisms (SNPs) in the highland East Asians (Sherpa and Tibetan) from the Simons Genome Diversity Project and ancient Tibetans from Nepal and Neolithic farmers from northeastern Qinghai-Tibetan Plateau from public databases. We subsequently merged our two datasets with other worldwide reference populations or eastern ancient Eurasians to gain new insights into the genetic diversity, population movements, and admixtures of high-altitude East Asians via comprehensive population genetic statistical tools [principal component analysis (PCA), multidimensional scaling plot (MDS), STRUCTURE/ADMIXTURE, f3, f4, qpWave/qpAdm, and qpGraph]. Besides, we also explored their forensic characteristics and extended the Chinese National Database based on STR data. We identified 231 alleles with the corresponding allele frequencies spanning from 0.0005 to 0.5624 in the forensic low-density dataset, in which the combined powers of discrimination and the probability of exclusion were 1–1.22E-24 and 0.999999998, respectively. Additionally, comprehensive population comparisons in our low-density data among 57 worldwide populations via the Nei’s genetic distance, PCA, MDS, NJ tree, and STRUCTURE analysis indicated that the highland Tibeto-Burman speakers kept the close genetic relationship with ethnically close populations. Findings from the 1240K high-density dataset not only confirmed the close genetic connection between modern Highlanders, Nepal ancients (Samdzong, Mebrak, and Chokhopani), and the upper Yellow River Qijia people, suggesting the northeastern edge of the TP served as a geographical corridor for ancient population migrations and interactions between highland and lowland regions, but also evidenced that late Neolithic farmers permanently colonized into the TP by adopting cold-tolerant barley agriculture that was mediated via the acculturation of idea via the millet farmer and not via the movement of barley agriculturalist as no obvious western Eurasian admixture signals were identified in our analyzed modern and ancient populations. Besides, results from the qpAdm-based admixture proportion estimation and qpGraph-based phylogenetic relationship reconstruction consistently demonstrated that all ancient and modern highland East Asians harbored and shared the deeply diverged Onge/Hoabinhian-related eastern Eurasian lineage, suggesting a common Paleolithic genetic legacy existed in high-altitude East Asians as the first layer of their gene pool.